An analysis of the effects of customer satisfaction and engagement on social media on repurchase intention in the hospitality industry - Mohammed Majeed; Charles Asare; Alhassan Fatawu; Aidatu Abubakari (Cogent Business & Management, 2022)
The purpose of this quantitative-deductive paper is to explore the link amongst customer satisfaction and engagement on social media on repurchase intention in the hospitality industry. The study was conducted on social media because, it is the fastest growing media in history. Data was collected from hotels in the three major business hub cities (Accra, Tamale and Kumasi) in Ghana. A total of 504 valid responses were obtained from respondents in the selected cities. SmartPLS software was used to analyze the data using (PLS-SEM) method. The results show that customer satisfaction has a positive and significant relationship on the dimensions of customer engagement. The three dimensions of customer engagement (contribution, consumption and creation) were found to significantly influence repurchase intention. Finally, two dimensions of engagement (contribution and consumption) were found to mediate the relationship between customer satisfactions and repurchase intention. The study is among the few to combine the COBRA model and Social Exchange Theory to assess the nexus between customers' engagement in an online environment and its linkages with satisfaction and repurchase intentions. Marketers should consider creating posts with photos, videos, and animation that consumers find entertaining and enjoyable, as this stimulates their desire to consume, contribute, and create content on social media pages for hotel brands.
Keywords: M31; 650; COBRA; Customer satisfaction; engagement; hospitality industry; Marketing; repurchase intention; social media